2012
DOI: 10.3126/jnps.v32i1.5339
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices in Kaski District, Pokhara

Abstract: Introduction: Children in developing countries are prone to infectious diseases due to insufficient and inappropriate feeding practices. Socio-demographic and socio-economic factors directly and indirectly play a role in influencing infant feeding practices. This study was conducted to assess the sociodemographic and economic factors associated with initiation of breastfeeding, complimentary feeding, and the various prelacteal feeds practiced in Kaski, Pokhara. Materials and Methods: In this prospective study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
4
1
Order By: Relevance
“…Similar findings were reported by NDHS survey 2011 and the other studies done in urban as well as rural communities in Nepal. 20,21 Our finding of colostrum use as a first feed is much higher than reported bystudies in Nigeria, a underdeveloped country like ours. 24 Another Nigerian studyin semi urban setting found exclusive breast-feeding rate to be low (33.0%).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Similar findings were reported by NDHS survey 2011 and the other studies done in urban as well as rural communities in Nepal. 20,21 Our finding of colostrum use as a first feed is much higher than reported bystudies in Nigeria, a underdeveloped country like ours. 24 Another Nigerian studyin semi urban setting found exclusive breast-feeding rate to be low (33.0%).…”
Section: Discussioncontrasting
confidence: 56%
“…Similar findings were also observed by other studies conducted in Nepal and India. [20][21][22][23] This study found that 87.3% of mothers used colostrum as first feed and the remaining percentage of mothers used infant formulas, cow/buffalos milk and water as first feed. Similar findings were reported by NDHS survey 2011 and the other studies done in urban as well as rural communities in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age at commencement of complementary feeds was found to be within the recommended age of 6 months by WHO. This is in consonance with findings of 5 months and 5.8 months in India and Benin City [ 17 , 18 ]. However, this is in contrast to studies in Kenya and Tanzania which found 2.9 months and 3.3 months as the mean ages for introduction of complementary feeds [ 12 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…Basnet et al found 51.6% of infant were stunted in urban area in Nepal who were not on EBF. 12 Whereas Mushaphi et al studied nutritional status of infants in the Vhembe District Limpopo Province found low LAZ in 18.9% cases, 78.4% normal LAZ and 2.7% high LAZ in their study. 11 Among the 52 infants in the present study, 3 (5.8%)…”
Section: Discussionmentioning
confidence: 77%